Discovery of Novel Bacterial Chalcone Isomerases by a Sequence‐Structure‐Function‐Evolution Strategy for Enzymatic Synthesis of (S)‐Flavanones. Issue 31 (30th June 2021) - Meinert, Hannes; Yi, Dong; Zirpel, Bastian; Schuiten, Eva; Geißler, Torsten; Gross, Egon; Brückner, Stephan I.; Hartmann, Beate; Röttger, Carsten; Ley, Jakob P.; Bornscheuer, Uwe T.
Abstract: Chalcone isomerase (CHI) is a key enzyme in the biosynthesis of flavonoids in plants. The first bacterial CHI (CHIera ) was identified from Eubacterium ramulus, but its distribution, evolutionary source, substrate scope, and stereoselectivity are still unclear. Here, we describe the identification of 66 novel bacterial CHIs from Genbank using a novel Sequence‐Structure‐Function‐Evolution (SSFE) strategy. These novel bacterial CHIs show diversity in substrate specificity towards various hydroxylated and methoxylated chalcones. The mutagenesis of CHIera according to the substrate binding models of these novel bacterial CHIs resulted in several variants with greatly improved activity towards these chalcones. Furthermore, the preparative scale conversion catalyzed by bacterial CHIs has been performed for five chalcones and revealed ( S )‐selectivity with up to 96 % ee, which provides an alternative biocatalytic route for the synthesis of ( S )‐flavanones in high yields. Abstract : Novel bacterial chalcone isomerases and their variants identified by a Sequence‐Structure‐Function‐Evolution (SSFE) strategy are able to convert chalcones to flavanones with diverse substrate scopes and strict ( S )‐stereopreference enabling a biocatalytic route to ( S )‐flavanones.